Asymptomatic UTI in pregnancy attending at tertiary care of Nepal - Yadav, Laxmi Kumari; Yadav, Ram Lochan (International Journal of Research in Medical Sciences, 2018)
Background: Urinary tract infections (UTI) during pregnancy issued by improper laboratory investigations situate women at risk of several detrimental complications. Untreated asymptomatic UTI (AUTI) may lead to pyelonephritis preterm birth, low birth weight, etc. Urine culture is used to confirm the diagnosis of UTI. Aim of this research was to carry out to find the prevalence of asymptomatic UTI and to establish antimicrobial drug susceptibility of the pathogens resulting asymptomatic UTI in pregnant women attending at tertiary care, Nepal. Methods: The urine samples were collected by mid-stream clean catch method from 600 pregnant women of age 15-45 years (mean age – 28.84 years) visiting for antenatal check up in the Department of Gynaecology and Obstetrics, Chitwan Medical College (CMC), a tertiary care of Nepal. All the urine samples were subjected to bio-physical, biochemical, microscopic, and microbiological analysis. The prevalence of UTI in three trimesters and in different age groups was obtained together with antimicrobial drug susceptibility tests. Results: On overall l51.83% of urine samples revealed with significant bacteriuria considered as the AUTI. On One- way ANOVA test, there was significant (P< 0.045) prevalence of AUTI when compared among different trimesters, though higher prevalence being in the first (40%) and second (45.33%) trimesters. The prevalence of AUTI was significant (P<0.004) among different age groups of the pregnancy. However, the most affectecd age groups were between 21-29 years. Escherichia coli were the most implicated organism (67.8%) followed by Klebsiella pneumonia (21.6%). The gram-negative bacteria (E. coli, K. pneumonia, and K. oxytoca) were more sensitive against Amikacin, Gentamycin, Meropenem, and Nitrofurantointhan. Other drugs whereas; gram positive bacteria (E. feacalis) had high susceptibility with Vancomycin. Conclusions: There was high incidence of AUTI among the pregnant ladies in the study region; therefore, microbial screening of urine of all pregnant women are must and should be included in the routine antenatal checkups to detect the AUTI to cut down and prevent the maternal and obstetric detrimental complications in them.